2016
DOI: 10.1007/s00705-016-2839-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biological characterisation of two novel pomo-like viruses associated with potato (Solanum tuberosum) fields in Colombia

Abstract: Potato is the fourth most important crop worldwide that is used as a staple food, after rice, wheat and maize. The crop can be affected by a large number of pathogens, including fungi, oomycetes, bacteria and viruses. Diseases caused by viruses are among the most important factors contributing to reduced quality and yield of the crop. Potato mop-top virus (genus Pomovirus) induces necrotic flecks in the tuber flesh and skin of potato in temperate countries. Spongospora subterranea is the vector of PMTV. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…S2), but a few covarying mutations in base-paired regions and one other mutation in a variable region make the strict conservation of the UAA anticodon peculiar. A sequencing error seems unlikely since the UAA leucine anticodon was present in all of the RNAs in multiple isolates of this recently-identified virus (Gil et al 2016). This anticodon triplet is only one nucleotide away from a valine anticodon (UAC is valine-compatible) 10 yet none of the three examples contain a valine codon, raising the question of why all three RNA segments have converted to the same non-valine anticodon.…”
Section: Tlss With Non-valine Anticodons Fail To Be Aminoacylatedmentioning
confidence: 94%
“…S2), but a few covarying mutations in base-paired regions and one other mutation in a variable region make the strict conservation of the UAA anticodon peculiar. A sequencing error seems unlikely since the UAA leucine anticodon was present in all of the RNAs in multiple isolates of this recently-identified virus (Gil et al 2016). This anticodon triplet is only one nucleotide away from a valine anticodon (UAC is valine-compatible) 10 yet none of the three examples contain a valine codon, raising the question of why all three RNA segments have converted to the same non-valine anticodon.…”
Section: Tlss With Non-valine Anticodons Fail To Be Aminoacylatedmentioning
confidence: 94%
“…Additionally the use of high-throughput sequencing for plant virus metagenomics (Boonham et al, 2014) increases the prospect of the discovery of as yet unknown viruses (Kreuze et al, 2009). Recent new additions to the list of potato-infecting viruses are Potato virus H, a new carlavirus species found to be widespread in several potato-growing areas in China (Li et al, 2013) and a new pomovirus Colombian potato soil-borne virus (Gil et al, 2016) that was found to coinfect potato with the pomovirus PMTV. Known viruses, Cherry leaf roll virus in Solanum acaule from Peru (Crosslin et al, 2010) and Tomato chlorosis virus, have been reported to infect potatoes in Spain and Brazil (Fortes & Navas-Castillo, 2012;Freitas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…No Seed transmission is not reported for pomoviruses (Mink, 1993;ICTV, 2012) Cannot be excluded Not reported, but other pomoviruses are transmitted by Spongospora subterranea (ICTV, 2012;Gil et al, 2016) Potexvirus PapMV Cannot be excluded Not reported, but seed transmission is reported for several other potexviruses (Mink, 1993) Yes Reported to be transmitted by several aphid species including Myzus persicae (Namba and Kawanish, 1966;Higa and Namba, 1971 (Manoussopoulos, 2000(Manoussopoulos, , 2001Pirone and Perry, 2002).…”
Section: Cpsbvmentioning
confidence: 99%
“…CPSbV Yes (Gil et al, 2016) Genomic sequence is available for the design of diagnostic primers (Chen et al, 2001;Wang et al, 2017) ELISA detection reagent set commercially available. Genus-specific molecular detection, identification by sequencing WPMV Yes Genomic sequence is available for the design of diagnostic primers …”
Section: Pomovirusmentioning
confidence: 99%